Lexico-Grammatical Analysis of Learners' Independent and Integrated Essays in EMI Context - Rahmi, Dery Singkawati; Kweldju, Siusana; Ivone, Francisca Maria (Jurnal Visi Ilmu Pendidikan, 2025)
A growing number of L2 novice writers in the EMI context lead the present study to examine the learner"™s lexico-grammatical features employment and a comprehensive description of the distinction of the L2 novice writing phenomena of interest in employing these features across independent and integrated tasks in the EMI context. The 24 samples of two task types from 12 learners were analysed. The present study used a quantitative approach and case study research design  to gain insights into  the detailed investigation and description. The phrasal features are frequently employed and repeated in integrated tasks to emphasize important features to support their ideas. Surprisingly, prepositional and finite adverbial phrases are frequently employed in independent tasks. Whereas, the noun + to clauses were revealed to be found only in integrated tasks to support their claim. Then, the other intermediate features are found as the least features produced across the two task types.